Disorders on cardiovascular parameters in rats and in human blood cells caused by Lachesis acrochorda snake venom. (September 2020) - Angel-Camilo, Karen Leonor; Guerrero-Vargas, Jimmy Alexander; Carvalho, Emanuella Feitosa de; Lima-Silva, Karine; de Siqueira, Rodrigo José Bezerra; Freitas, Lyara Barbosa Nogueira; Sousa, João Antônio Costa de; Mota, Mario Rogério Lima; Santos, Armênio Aguiar dos; Neves-Ferreira, Ana Gisele da Costa; Havt, Alexandre; Leal, Luzia Kalyne Almeida Moreira; et al.
Abstract: In Colombia, Lachesis acrochorda causes 2–3% of all snake envenomations. The accidents promote a high mortality rate (90%) due to blood and cardiovascular complications. Here, the effects of the snake venom of L. acrochorda (SVLa) were analyzed on human blood cells and on cardiovascular parameters of rats. SVLa induced blood coagulation, as measured by the prothrombin time test, but did not reduce the cell viability of neutrophils and platelets evaluated by the 3-(4, 5-dimethylthiazol-2yl)-2, 5-diphenyl tetrazolium bromide (MTT) reduction assay and by the lactate dehydrogenase (LDH) enzyme assay. In fact, SVLa increased the absorbance in tests made with platelets subjected to the MTT assay. SVLa induced platelet aggregation whose magnitude was comparable to that of the positive control adenosine diphosphate (ADP), and occurred earlier with increasing SVLa concentration. Acetylsalicylic acid (ASA, a cyclooxygenase inhibitor) or clopidogrel (an ADP receptor blocker) inhibited the aggregating effect of SVLa. Inhibition of SVLa-elicited platelet aggregation also resulted from the treatment with disodium ethylenediaminetetraacetate (Na2 -EDTA; metalloproteinase inhibitor) and with 4-(2-aminoethyl) benzenesulfonyl fluoride hydrochloride (AEBSF, serine protease inhibitor). In isolated right atrium of rats, SVLa increased slightly, but significantly, the magnitude of the spontaneous contractions and, in isolated rat aorta, SVLa relaxed KCl- or phenylephrine-induced contractions. In vivo, SVLa induced hypotension and bradycardia in rats, with detection of hemorrhage in pulmonary and renal tissues. Altogether, under experimental conditions, SVLa induced blood coagulation, platelet aggregation, hypotension and bradycardia. Part of the effects presented here may be explained by the presence of snake venom metalloproteinases (SVMPs) and snake venom serine proteases (SVSPs), constituents of SVLa. Highlights: Snakebite accidents due to Lachesis acrochorda (LA) have a high mortality rate. Blood coagulation, hypotension and bradycardia may occur in patients after the bite. In vitro, the LA venom induced coagulant effect and platelet aggregation. In vivo, hypotension, bradycardia and death were confirmed at low doses. Metalloproteases and serinoproteases seem to be involved in the venom effects.